Theoretical Studies on Mechanism of Inactivation of Kanamycin A by 4′-O-Nucleotidyltransferase - Martí, Sergio; Bastida, Agatha; Świderek, Katarzyna (Frontiers in Chemistry, 2019)
This work is focused on mechanistic studies of the transfer of an adenylyl group (Adenoside-5’-monophosfate) from adenosine 5’-triphosphate (ATP) to a OH-4’ hydroxyl group of an antibiotic. Using hybrid quantum mechanics / molecular mechanics (QM/MM) techniques, we study the substrate and base-assisted mechanisms of the inactivation process of the kanamycin A (KAN) catalyzed by 4’-O-Nucleotidyltransferase(ANT(4’)), an active enzyme against almost all aminoglycosides antibiotics. Free energy surfaces, obtained with Free Energy Perturbation methods at M06-2X/MM level of theory, show that the most favorable reaction path presents a barrier of 12.2 kcal∙mol-1 that corresponds to the concerted activation of O4’ from KAN by Glu145. In addition, the primary and secondary 18O kinetic isotope effects (KIEs) have been computed for bridge O3α, and non-bridge O1α, O2α and O5’ atoms of ATP. The observed normal 1º-KIE of 1.2% and 2º-KIE of 0.07% for the Glu145-assisted mechanism are in very good agreement with experimentally measured data. Additionally, based on obtained results the role of an electrostatic and compression effects in enzymatic catalysis is discussed.